Acute Hospital Admission for Stroke Is Characterised by Inactivity. (11th February 2020) - Sheedy, R.; Kramer, S. F.; Johnson, L.; Shields, N.; Churilov, L.; Cadilhac, D. A.; Bernhardt, J.
Abstract : Background . Measuring physical activity behaviours of stroke survivors in the inpatient setting is challenging. Authors of observational studies of early poststroke report that stroke survivors are "inactive and alone". Using activity monitoring devices may help refine clinical practice and inform therapeutic activity targets. Aim. To measure the physical activity behaviour of stroke survivors during acute inpatient hospitalisation. We hypothesized that greater levels of inactivity would be positively associated with stroke severity and age. Method . Using a cross-sectional study design, consecutive stroke patients admitted to an acute stroke unit (Geelong, Australia) and recruited within 48 hours of admission had their physical activity recorded using an ActivPAL™ accelerometer device over a minimum of 3 days. Activity was categorised as time spent inactive (lying or sitting), standing, or stepping. The number of steps per day was recorded. Demographic and ActivPal™ data are described. Results . Seventy-eight stroke survivors were recruited of whom 54 had complete data for 3 days, all starting within 2 days poststroke. Of the 54 participants, 32 had a mild stroke, 17 moderate, and five severe stroke. Nine were able to walk independently at admission. The median age was 82.5 years (interquartile range (IQR) 74-86), 26 were female. On average, during their inpatient stay, participants spent a median of 98% of their admission inactive. A median of 18 minutes per day was spent standing and less than a minute per day was spent walking amounting to a median of 169 steps taken per day. Conclusion . The ActivePal™ device was feasible to use in an acute stroke setting. We observed high levels of inactivity in the first days post-stroke, highlighting the ongoing challenge of promoting activity in the acute stroke period. To our knowledge, this is the largest study to provide objective data on time spent upright, walking, and sedentary using accelerometer data in an acute stroke setting.